Tantangan Implementasi Merdeka Belajar Kampus Merdeka Pada Mahasiswa Universitas Sarjanawiyata Tamansiswa - Widodo Budhi; Uum H Chaerunisak; Uswatun Khasanah; Ajeng T Putri; D Dinarsih; Nurul Ainun Fadhya; C Chichhi; Siti Rochmiyati (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
Changes to the higher education curriculum are carried out periodically. This curriculum change must involve both internal and external stakeholders and must be in accordance with the National Higher Education Standards. The problem is that the Independent Learning Curriculum policy has been implemented by universities, but the 8 independent learning programs offered by the Ministry of Education and Culture have not shown satisfactory results. The challenge of implementing an independent learning curriculum from a student's point of view has not been done much, even though students are the stakeholders who are most affected by the implementation of this curriculum. In connection with these conditions, the purpose of this study is to describe the challenges of students in the MBKM program at the University of Sarjanawiyata Tamansiswa. The stages in this research use case study research with a mixed approach. The quantitative stage was carried out by means of a survey to students at the University of Sarjanawiyata Tamansiswa about the perception of the implementation of the independent learning curriculum. This quantitative stage was analyzed descriptively quantitatively. In this qualitative stage, the students who were interviewed were conducted by purposive sampling. At the qualitative stage, it was done by analyzing the documents and the results of interviews about the independent learning of the independent curriculum. The results showed that the MBKM including its documents had been socialized to students. Although the results of the socialization did not produce a good effect because students did not understand about the number of semesters that could be equated in the form of MBKM outside their university, they had a positive perception of the usefulness of MBKM activities.